Medroxyprogesterone acetate, enoxaparin and pentoxyfylline cause alterations in lipid peroxidation, paraoxonase (PON1) activities and homocysteine levels in the acute oxidative stress in an experimental model of spinal cord injury - Topsakal, C; Kilic, N; Erol, FS; Kaplan, M; Akdemir, I; Tiftikci, M; Gursu, F (Springer Wien, 2002)
Background Effects of medroxyprogesterone acetate, enoxaparin and pentoxyfylline on lipid peroxidation, antioxidant defence system, paraoxonase activities, and homocysteine levels in an experimental model of spinal cord injury were investigated. Method. Sixty-three male albino Wistar rats were anaesthetized by 400 mg/kg chloral hydrate and divided into 5 groups. G1 (n 7) = control group provided the baseline levels. G2-G5 underwent T3-6 total laminectomies and spinal cord injuries by clip compression at T4-5 levels. Medications were applied to G3-G5 right after the injury. Hence, G2 constituted laminectomy + injury (lam + I); G3 = lam + I + medroxyprogesterone acetate (MPA), G4 = lam + I + enoxaparin (E), and G5 - lam + I + pentoxyfylline (P) groups. Animals were decapitated either at the 1st or 4th hour after injury. Tissue and blood malonyldialdehyde (MDA) and plasma homocysteine and erythrocyte superoxide dismutase (SOD) levels, and erythrocyte glutathione peroxidase (GSH-Px) and plasma paraoxonase (PON1) activities were assayed. SPSS 9.0 program was used for statistical analysis and graphics. Intergroup comparisons were made by Bonferroni corrected Mann Whitney U test (P < 0.025), and intragroups comparisons by Wilcoxon Rank test (P < 0.03). Findings. In intergroup comparison, G1-G2, G1-G3, G1-G5, G2-G3, G2-G4, and G4-5 groups differed from each other for all parameters (P < 0.025, MWU) except for G4-G5 4th hour MDA levels. G1-G4 was similar for all 1st hour parameters (P > 0.025, MWU), but different for 4th hour (P < 0.025, MWU) except for GSH-Px and SOD levels. For G2-G5, all parameters for 1st and 4th hour were similar except for 4th PON1, Hey and SOD levels. For G3-G4, all 1st hour parameters were different from each other (P < 0.025, MWU); whereas all 4th hour parameters were similar except for SOD level. For G3-G5, all parameters at 1st and 4th hour were similar except for 4th hour GSH-Px, PON1, and Hey. In intragroup comparison, all parameters differed from each other at all times (P < 0.03, WRT) except for 1st hour G4 MDA, Hey and SOD levels compared to basal levels. Interpretation. In injury groups, plasma Hey levels decreased and PONI activities increased as erythrocyte SOD level and GSH-Px activities decreased in parallel to increases of tissue and blood MDA levels. These changes were relatively suppressed by MPA, enoxaparin and pentoxyfylline administrations at varying degrees. Enoxaparin was the most powerful agent, particularly at 1st hour. MPA was also effective, particularly at 4th hour. Pentoxyfylline despite having slight effect at 4th hour, was not effective according to both control and injury groups. Enoxaparm and MPA can be used in the treatment of spinal cord injuries. PON1 and Hey are helpful in monitoring the antioxidant defence system as well as SOD and GSH-Px, both in injury and medically treated groups.
Keywords: Molecular-Weight Heparin; Oxygen Free-Radicals; Reduces Brain Edema; Superoxide-Dismutase; Serum Paraoxonase; Induced Hyperhomocysteinemia; Glutathione-Peroxidase; Rheumatoid-Arthritis; Receptor Antagonists; Plasma Homocysteine